Evidence-based recommendations for advancing the chronic pelvic pain syndrome management by the paradigm change from reactive symptom suppression to proactive 3PM-guided patient-centered care - Ousman Bajinka; Lamarana Jallow; Na Li; Christian Kuhn; Walther Kuhn; Ivana Stetkarova; Olga Golubnitschaja; Xianquan Zhan (EPMA Journal, 2026)
Abstract Chronic pelvic pain syndrome (CPPS) encompasses a heterogeneous group of debilitating conditions including interstitial cystitis/bladder pain syndrome (IC/BPS), chronic abacterial prostatitis, endometriosis, and pelvic congestion syndrome, among others. Despite advances in symptomatic management, CPPS remains challenging due to its multifactorial etiology, complex phenotypes, and poor response to conventional reactive treatments. On the other hand, sympathetic overdrive phenotype (SOP) carriers frequently suffer from increased stress sensitivity, chronic sterile inflammation, pain chronification, and mitochondrial stress – all considered the key CPPS/SOP shared pathomechanisms. Further, the dominant vasoconstriction, altered sense regulation (e.g. the reduced feeling of thirst potentially resulting in systemic dehydration) as well as altered multi-drug resistance protein profiles characteristic for SOP (e.g. exemplified by the Flammer syndrome) may predispose affected individuals to the therapy resistance such as CPPS patients with vulvar-vaginal dryness and abacterial prostatitis. This review article highlights the central role of SOP, systemic mitochondrial stress as well as gut and urinary microbiome alterations – all, per evidence, are considered systemic modifiable risk factors of the CPPS manifestation, disease progression, and therapy resistance. The article introduces 3PM-guided patient-centered solutions aiming to improve life quality and individual outcomes in the CPPS patient cohort. Non-invasive mitochondria-based biosensorics, e.g. applied via the tear fluid analysis, and digital health monitoring, per evidence, enable early health risk assessment and patient stratification at the level of reversible damage to health. Recommended targeted preventive strategies encompass individually adapted lifestyle modifications, modulation of the stress-associated mitochondrial homeostasis, and application of supportive nutraceuticals. Personalized 3PM-guided treatment algorithms transform CPPS management into the patient-centered, cause-oriented and cost-effective proactive care, protecting vulnerable individuals against health-to-disease transition and preventing disease progression in stratified patients.